Incoterms dalam Perjanjian Perdagangan Internasional - Adri Wijaya; Andi Yenni Rakhman Putri; Ahmad Dzulfahmi Saleh (Jurnal Litigasi Amsir, 2022)
This research aims to study and analyze the position of International Commercial Terms (Incoterms) as international customary law in international trade agreements as well as to study and analyze the rights and obligations of the exporters and importers concerning the use of Incoterms in an international trade agreement. The benefits expected from the results of this research are as a contribution of thoughts in the field of legal studies, especially in connection with international trade law for the businessmen in the sector of international trade and the government in making legislation concerning international trade. The method of this research is normative legal research by studying legal resources (primary, secondary, and tertiary legal resources) which are relevant to the legal issues being studied. The approach used is analytical. The results of this research point out that the legal force of Incoterms in international trade agreements is derived from customary law and international customs which have a position as law. Incoterms are a source of international trade law. However, the legal force of Incoterms as international customary law is not equal to the legal force of International Agreements such as Convention, Treaty, Charters, Agreement, Covenant, Protocol, Fact, etc. So, in practice, the exporters and importers frequently experience that the provisions of the Incoterms which have been agreed upon by the parties are then violated by one of the parties because the Incoterms are not yet perfectly regulated. Incoterms still raise problems in their application in the field because there are vague norms concerning the scope and limits of responsibilities of each party, namely, the exporters and importers.